Between Figure and Ground: Seeing in Premodernity - Quené, Saskia C (De Gruyter, 2025)
The terms "figure" and "ground" became fundamental to art-historical analysis. But is this dichotomy suited to describe premodern art and? This volume calls into question long-standing habits of seeing and understanding figure-ground relations, expands art historical vocabularies, and challenges anachronistic attachments to modernist paradigms